THE ROLE OF MANAGEMENT INFORMATION SYSTEMS IN APPLICATIONS E-LEARNING AT UBHARA JAYA - Faeni, Dewi Puspaningtyas; Wijayanti , Ika (Komunitas Menulis dan Meneliti (Kolibi), 2024)
The word electronic in e-learning means taking advantage of the addition of technological elements to the learning process so that it involves various hardware, software, and other electronic processes. Experience in this context describes the provision of broad and varied access to all students to learn, adjusted to the willingness of time; place; manner; material; as well as the available environment. Extended means extending and expanding learning opportunities for students, not limited to specific programs but lasting throughout life. Expanded means learning is open to everyone, with a wider range of materials and topics so that learning will not be hampered by the availability of funds. E-learning is very beneficial for students in learning learning materials because this technology allows them to learn flexibly wherever and whenever needed. Materials that are poorly understood by students at school can be relearned through elearning so that it will be easier for students with more time and opportunities to understand well because it is not limited like at school.